2014
DOI: 10.4172/2157-7471.1000231
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly and Safe Role of Juniperus procera in Controlling of Fungal Growth and Secondary Metabolites

Abstract: Radial growth Aspergillus flavus and Fusarium oxysporum was determined on medium amended with Juniperus procera methanolic extract. The radial growth of A. flavus and F. oxysporum was significantly reduced at 150 and 200 mg. The precentage of reduction was 16.55%, 48.54% and 48.64%, 59.86% for A. flavus and F. oxysporum, respectively. However, addition of J. procera extract to Carbomar significantly reduced radial growth compared with using Carbomar alone. On the other hand, with addition of the J. procera ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Our results partially agreed with Ahmed et al (2021) , who recorded the absence of caffeic acid, ellagic acid, kaempferol, and apigenin but chlorogenic acid, catechin, rutin, and quercetin occurred in the extract of A. graveolens . These variances in the flavonoid and phenolic contents may arise from some genetic and ecological differences besides the nutritional and cultivation status of the plants, besides the extraction methods and the used solvents ( Ghany, 2014 ). Most of the detected compounds, either phenolic or flavonoid, documented their validity in the various biological activities as mentioned in the scientific papers.…”
Section: Resultsmentioning
confidence: 99%
“…Our results partially agreed with Ahmed et al (2021) , who recorded the absence of caffeic acid, ellagic acid, kaempferol, and apigenin but chlorogenic acid, catechin, rutin, and quercetin occurred in the extract of A. graveolens . These variances in the flavonoid and phenolic contents may arise from some genetic and ecological differences besides the nutritional and cultivation status of the plants, besides the extraction methods and the used solvents ( Ghany, 2014 ). Most of the detected compounds, either phenolic or flavonoid, documented their validity in the various biological activities as mentioned in the scientific papers.…”
Section: Resultsmentioning
confidence: 99%
“…C. lunata growth was inhibited by 88.42 and 37.50 % when growth medium was treated with J. procera and A. marina extracts respectively. Recently, Abdelghany [27] reported the antifungal effect of J. procera crude extract against growth of Aspergillus flavus and Fusarium oxysporum. Surprisingly, A. marina extract at low concentrations induced the vegetative growth of C. lunata (Figure 2), but it suppressed the fungal sporogenisis.…”
Section: Resultsmentioning
confidence: 99%
“…[24]. Juniperus species have been extensively investigated as a source of natural products with potential antibacterial, antifungal and insecticidal activities [25][26][27]. Mariana and Camelia, [28] reported that Juniper oil has inhibition action against Aspergillus niger, Fusarium oxysporum, Monascus purpureus and Penicillium hirsutum.…”
Section: Introductionmentioning
confidence: 99%
“…Plant activators such as ergosterol [24], methylesterase [25], abscisic acid [26], gibberellic acid, salicylic acid [27] and SO 4 2- [28] and inhibitors such as coronatine [29], aflatoxin [30], aspergillic acid [31], fusaric acid [32] and CA1P [28] were docked. Out of all the activators tested for RuBisCO activity, ergosterol was found to have high binding affinity to RuBisCO LSU and SSU, followed by methylesterase (Table 4).…”
Section: Protein-binding Sitesmentioning
confidence: 99%